2018
DOI: 10.1002/macp.201700579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chain Transfer Agent and Temperature on Branching and β‐Scission in Radical Polymerization of 2‐Ethylhexyl Acrylate

Abstract: Poly(2‐ethylhexyl acrylate) is synthesized by conventional radical bulk polymerization both with and without 1‐dodecane thiol as chain transfer agent (CTA) at temperatures from 4 to 140 °C. Electrospray‐ionization mass spectrometry is used to analyze the polymer. This reveals the occurrence of significant β‐scission at high temperature and confirms the presence of CTA‐capped polymers at all temperatures, as well as combination products from 4 to 65 °C. Subsequent 13C melt‐state NMR analysis allows quantificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Termination by combination and disproportionation kinetic rate coefficients for BA and MMA copolymerizations were also taken from WATPOLY, as shown in Equations (22) and (23) [6,31].…”
Section: Terminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Termination by combination and disproportionation kinetic rate coefficients for BA and MMA copolymerizations were also taken from WATPOLY, as shown in Equations (22) and (23) [6,31].…”
Section: Terminationmentioning
confidence: 99%
“…Although MMA is a widely studied monomer, there are no reports that we are aware of where backbiting is important for this monomer. In the case of EHA, there is evidence that backbiting may become important at temperatures in the range of 100 to 140 • C [23]. Since the experiments used in our study were conducted at 60 • C, it is well justified to neglect backbiting for EHA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These promote polymer chain terminations and formation of new chains, thus resulting in low molecular weights. According the bibliography, this effect is called the "patching effect" [17,18]. Plessis and Arzamendi [19] showed that by increasing the concentration of the chain transfer agent from 0.00 to 0.15% the gel content decreased from 55 to 0%, as did the average molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…39 Mass spectrometry analyses and in particular ESI-MS proved to be important for getting more insight into the β scission and subsequent migration mechanism. 28,33,34,[39][40][41] The goal of this work was to carefully analyze the products obtained from free radical acrylate polymerizations at temperatures of at least 120°C and to identify the low molar mass scission products. Studying free radical polymerizations appeared particularly important due to its high technical relevance.…”
Section: Introductionmentioning
confidence: 99%